2020
DOI: 10.1590/1980-5373-mr-2020-0214
|View full text |Cite
|
Sign up to set email alerts
|

Building and Testing a Spin Coater for the Deposition of Thin Films on DSSCs

Abstract: A low cost spin coater was constructed in this work for the deposition of thin films of titanium dioxide (TiO 2 ) on conductive substrate of FTO (fluoride doped tin oxide) with application on dye sensitized solar cells. The results showed a 95% precision between the speed values obtained by the software of C#sharp language and the spin values observed directly on the device. The TiO 2 films deposited through the spin coater with different angular speeds were characterized by UV-Vis optical spectrum, scanning e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Any machine that works with nanoscale dimensions must be designed with high accuracy, so it is necessary to calculate the effects of rotation in this work on the thickness and homogeneity of the film 23 . As well, the spin coating machine needs to be free from the vibration effects to obtain films with high homogeneity, regardless of the number of coating layers.…”
Section: Substrate Holdermentioning
confidence: 99%
“…Any machine that works with nanoscale dimensions must be designed with high accuracy, so it is necessary to calculate the effects of rotation in this work on the thickness and homogeneity of the film 23 . As well, the spin coating machine needs to be free from the vibration effects to obtain films with high homogeneity, regardless of the number of coating layers.…”
Section: Substrate Holdermentioning
confidence: 99%
“…The results indicated that the film with 12.73 μm had better performance of ƞ = 6.07%. In other work, (Teixeira ES et al, 2020) deposited thin films of TiO 2 by spin coating with different thickness (65.90, 90.17, 106.7 μm). The results indicated that the cell assembled with TiO 2 of thickness 65.90 μm presented ƞ = 12.74%.…”
Section: Sem (Scanning Electron Microscopy) and Eds (Energy Dispersiv...mentioning
confidence: 99%